Public Relations Strategy in Developing School Image at SMA Negeri 1 Jayapura - Erwin Arianto; Saraswati S; Desi Islamiati (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This abstract discusses the development of SMA Negeri 1 Jayapura as an educational institution that has demonstrated significant improvement in both academic and non-academic achievements, as well as in student enrollment. The background of this study emphasizes the importance of public relations strategies in building a positive school image amid competition among educational institutions. The purpose of this research is to analyze the implementation of public relations strategies, identify supporting and inhibiting factors, and evaluate their impact on public perception of the school. This study employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and verification using triangulation techniques to ensure the validity of the findings. The results show that public relations strategies covering alumni management, human resource development, publications, and event organization are collaboratively designed with the school principal by considering various aspects of school image building. The implementation of these strategies is carried out systematically through promotion in print media, electronic media, and social media, as well as through communication and public outreach. The implications of this study indicate that integrated and consistent public relations strategies can enhance the school’s positive image and strengthen public trust, thereby contributing to the competitiveness of educational institutions.